Answer:
a^2 + b^2 = c^2
a^2 + 24^2 = 25^2
a=7
Step-by-step explanation:
Answer: 2.3
Step-by-step explanation:
First dstribute the -5
-8p-5+5p=0
Add like terms
-3p-5=0, add 5 on both sides
-3p=5, divide -3 on both sides
p=-5/3
Answer:
6x² - 19x + 10
Step-by-step explanation:
Given
(3x - 2)(2x - 5)
Each term in the second factor is multiplied by each term in the first factor, that is
3x(2x - 5) - 2(2x - 5) ← distribute both parenthesis
= 6x² - 15x - 4x + 10 ← collect like terms
= 6x² - 19x + 10
60,000+ 5,000 + 50 + 8 and sixty five thousand fifty eight